О судьбе удмуртского народа - Пономарев Карл Александрович (Удмуртия, 2018)
Экземпляры: аб. ЦБ (20190910) / Инвентарный номер: 7210 / Цена: / Сис.шифр: 63.3(2Рос.Удм) / Авт.знак: П 56 / ГРНТИ: 03.23 / ББК: 63.3(2Рос.Удм)